Recent progress on porous MOFs for process-efficient hydrocarbon separation, luminescent sensing, and information encryption. Issue 6 (4th January 2022) - Zhao, Dian; Yu, Kuangli; Han, Xue; He, Yabing; Chen, Banglin
Abstract : This feature article highlights the recent, important progress on multifunctional MOF materials for their application in hydrocarbon separation, luminescent sensing, and information encryption. Abstract : Metal–organic frameworks (MOFs), as an emerging class of porous materials, excel in designability, regulatability, and modifiability in terms of their composition, topology, pore size, and surface chemistry, thus affording a huge potential for addressing environment and energy-related challenges. In particular, MOFs can be applied as porous adsorbents for the purification of industrially important hydrocarbons through certain process-efficient separation schemes based on selectivity-reversed adsorption and multicomponent separation. Moreover, the vast combination possibilities and controllable and engineerable luminescent units of MOFs make them a versatile platform to develop functionally tailored materials for luminescent sensing and optical data encryption. In this feature article, we summarize the recent progress in the use of porous MOFs for the separation and purification of acetylene (C2 H2 ) and ethylene (C2 H4 ) based on selectivity-reversed adsorption and multicomponent separation strategies. Moreover, we highlight the advances over the past three years in the field of MOF-based luminescent materials for thermometry, turn-on sensing, and information encryption.